Fucosyltransferase 2: A Genetic Risk Factor for Intestinal Diseases - Hu, Mingyang; Zhang, Xiyun; Li, Jinze; Chen, Luotong; He, Xiaolin; Sui, Tingting (Frontiers in Microbiology, 2022)
The fucosyltransferase 2 gene (FUT2) mediates the synthesis of histoblood group antigens (HBGA) that occur in vivo from multiple organs, particularly on the surface of intestinal epithelial cells and body fluids. To date, many studies have demonstrated that the interaction of HBGA with the host microbiota is the cause of pathogenesis of intestinal diseases, making FUT2 non-secretor a risk factor for IBD due to the lack of HBGA. Since HBGA also acts as an attachment site for norovirus (NoV) and rotavirus (RV), the non-secretor becomes a protective factor for both viral infections. In addition, the interaction of norovirus and rotavirus with symbiotic bacteria has been found to play an important role in regulating enteroviral infection in IBD. Given the current incomplete understanding of the complex phenomenon and underlying pathogenesis of intestinal diseases such as IBD, it has recently been hypothesized that the FUT2 gene regulates intestinal bacteria through attachment sites, may help to unravel the role of FUT2 and intestinal flora in the mechanism of intestinal diseases in the future and provide new ideas for the prevention and treatment of intestinal diseases through more in-depth studies.